An Economic and Legal Evaluation of Peasantism and Land Issue in the Second Constitutionalist Period - Ballı, Ergül (Journal of Applied And Theoretical Social Sciences, 2022)
The 2nd Constitutional Monarchy period, which covered the years between 1908 and 1918, was a period, during which reformist steps were taken in the Ottoman economic and social life. Union and Progress, the dominant political party of the period, developed a reformist style on the peasant and land issue of the society to which it belonged. The Unionists, made political promises such as distribution of land to landless village folk and to village folk possessing a very small amount of land, provision of affordable credits and elimination of the tithe tax or improvement of the tithe tax collection method. While, it had adopted a political discourse defending small peasantry before coming into power, the Union and Progress, is, without any doubt, a political party defending the class interests of Muslim-Turkish bourgeoisie. After coming into power, it fell under the influence of the dominant classes and adopted an agriculture policy, while being populist in discourse, actually in factor of large taxpayers in practice. Also, through the provisional laws, which went into effect, starting from the year 1913, it re-formulated the land laws in favor of large farmers, engaged in modern agriculture. The purpose of the present study is to analyze the economical and social effects of the Union and Progress’s peasant policy, along with its continuity and rupture elements.